2014
DOI: 10.1590/1807-3107bor-2015.vol29.0001
|View full text |Cite
|
Sign up to set email alerts
|

Preference for using posts to restore endodontically treated teeth: findings from a survey with dentists

Abstract: The aim of this study was to evaluate if clinical experience, whether in relation to length of practice time and/or level of specialization influences the dentist's preference for using posts to restore endodontically treated teeth. A cross sectional study was carried out using a questionnaire with dentists (n = 276) in Pelotas, southern Brazil. Data were collected regarding clinical experience, post-graduate training, and variables related to restorations (posts/cements and use of rubber dam) for endodontical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 29 publications
(39 reference statements)
2
27
0
1
Order By: Relevance
“…These findings corroborate previous findings showing that cast metal posts are still used for dentists [11]. It is obvious that cast metal posts are the gold standard in literature to restore ETT with large coronal destruction as they present high success rates in longitudinal studies [16,19].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings corroborate previous findings showing that cast metal posts are still used for dentists [11]. It is obvious that cast metal posts are the gold standard in literature to restore ETT with large coronal destruction as they present high success rates in longitudinal studies [16,19].…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study showed a difference in the choices of materials/techniques to restore ETT between dentists and students. Literature has shown that some factors could influence the choices of materials and techniques as workplace, time since graduation, post graduate training and capability to keep updated [9][10][11]13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These posts require adequate luting material to achieve successful clinical performance, and the use of resin-based luting agents has increased over the last decades (4). When eugenolbased sealers are prepared, eugenol is mixed with zinc oxide in the presence of water, and a chelation reaction occurs, resulting in a zinc eugenolate matrix with unreacted eugenol molecules trapped inside.…”
mentioning
confidence: 99%